Causa más frecuentes en la pérdida dental basada en percepciones de pacientes mayores de 30 años y criterios clínicos de profesionales odontológicos en la ciudad de Quito - Flores Gómez, Jonathan Alexis (2016)
The present titration work was proposed to determine the causes of dental loss, but taking into account the opinion of patients as well as dental professionals. Dental loss has been related to several factors, which were analyzed in this study, the data found suggest that the main cause of dental loss is caries coinciding with several studies found in Latin America giving as a result that the reality is similar, or studies In Ecuador but with differences in the amount of sample, for this information was collected through two surveys, one to the patients and another to the same dentists that allowed to determine the causes for the dental loss, calculation of the sample was performed on a base To the random sampling formula, so it was applied to 384 patients and 303 dentists from the city of Quito, the data collected were collected through the data collection tab respectively. What was found was that: the perception of cause of dental loss of patients was caries with a representative percentage of 77 percent, which makes it the main cause. Similarly, it has been determined that patients with more loss of dental pieces are people between 30 and 50 years, but in particular the people of 35 years are the ones with the most loss of parts. The women are slightly a population with greater loss of pieces with a percentage of 58 percent. Trauma is considered the second most important cause of dental loss, this is mainly found in men. These data were collected from patients, while: Dentists also consider that the main cause for the loss of pieces are caries with a total of 42 percent. With advances in technology and the specialization of the dental career there are other less invasive treatment options that favor the preservation of dental pieces in the mouth, for example: root canals, crowns, incrustations. What was also analyzed in this study was the action that the professional would take in a piece with 1.5mm of healthy dentin close to the pulp and most professionals decided to perform endodoncias in 54 percent instead of remineralizing the piece.